2013
DOI: 10.4161/auto.26838
|View full text |Cite
|
Sign up to set email alerts
|

Q6, a novel hypoxia-targeted drug, regulates hypoxia-inducible factor signaling via an autophagy-dependent mechanism in hepatocellular carcinoma

Abstract: Tumor hypoxia underlies treatment failure and yields more aggressive and metastatic cancer phenotypes. Although therapeutically targeting these hypoxic environments has been proposed for many years, to date no approaches have shown the therapeutic value to gain regulatory approval. Here, we demonstrated that a novel hypoxia-activated prodrug, Q6, exhibits potent antiproliferative efficacy under hypoxic conditions and induces caspase-dependent apoptosis in 2 hepatocellular carcinoma (HCC) cell lines, with no ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 29 publications
2
28
0
Order By: Relevance
“…Autophagy plays an important role in the process of hypoxia. Recent studies have indicated that HIF-1 regulates the autophagy under hypoxia [20]. On the contrary, it was reported that oxygen deprivationinduced autophagy does not require HIF-1 activity.…”
Section: Discussionmentioning
confidence: 96%
“…Autophagy plays an important role in the process of hypoxia. Recent studies have indicated that HIF-1 regulates the autophagy under hypoxia [20]. On the contrary, it was reported that oxygen deprivationinduced autophagy does not require HIF-1 activity.…”
Section: Discussionmentioning
confidence: 96%
“…Nowadays, several agents affecting HIF-1α signaling have been introduced, with varying results depending on a cancer's HIF-α phenotype [43, [186][187][188]. They include antiangiogenic agents, such as inhibitors of vascular endothelial growth factor (VEGF), mTOR, and heat shock protein 90 inhibitors, or agents that restore or activate PHD enzyme activity.…”
Section: Conclusion and Future Therapeutic Perspectivesmentioning
confidence: 99%
“…Chemo-therapy has been used for over 30 years but resistance remains a significant barrier for both cytotoxic and targeted agents, and therefore has triggered great research efforts worldwide for new treatment modalities that might be applicable to this cancer [4,5]. Due to hypovascularity, the hepatic tumors are significantly more hypoxic than adjacent normal tissues (ANT) [6,7]. To adapt to this unfavorable condition, cancer cells would activate various biological behaviors, such as angiogenesis, and migration to less hypoxic and more nutritious areas [8][9][10].…”
Section: Introductionmentioning
confidence: 99%